2021
DOI: 10.1007/s12020-021-02855-2
|View full text |Cite
|
Sign up to set email alerts
|

Higher SARS-CoV-2 viral loads correlated with smaller thyroid volumes on ultrasound among male COVID-19 survivors

Abstract: Purpose Thyroid dysfunction, including thyroiditis, is well recognized in COVID-19 patients. We evaluated thyroid ultrasonographic features among COVID-19 survivors, which are less well known. Methods Adult COVID-19 survivors without known thyroid disorders who attended dedicated COVID-19 clinic underwent thyroid ultrasonography and assessment of thyroid function and autoimmunity. Adults admitted for acute non-thyroidal surgical problems and negative for COVID-19 were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 33 publications
2
22
1
Order By: Relevance
“…The mechanisms regarding the effect of COVID-19 on the thyroid gland are not yet fully clear. As we found in our study, the authors did not find any association with systemic inflammation markers such as CRP and the thyroid gland volume [17]. We did not detect any relationship between the inflammatory markers, gender, and severity of disease with thyroid gland volume.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…The mechanisms regarding the effect of COVID-19 on the thyroid gland are not yet fully clear. As we found in our study, the authors did not find any association with systemic inflammation markers such as CRP and the thyroid gland volume [17]. We did not detect any relationship between the inflammatory markers, gender, and severity of disease with thyroid gland volume.…”
Section: Discussioncontrasting
confidence: 55%
“…In a study by Lui et al [17], 79 patients were evaluated for a median of 2 months after the diagnosis of COVID-19. The authors found that thyroid gland volume was lower than in control subjects, although the difference did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid gland volume was signi cantly lower in patients with a higher viral load and in men. No correlation was found between in ammatory markers during acute COVID-19 infection and thyroid gland volume [22]. We could not evaluate viral load since our study was observational and this is a limitation for this study.…”
Section: Discussionmentioning
confidence: 89%
“…They had a mean (SD) age of 67.5 ± 13.8 years and were predominantly males (N=124, 68%). The NEWS2 score assessed at hospital admission was low in 84 (47%), medium in 60 (33%) and high in 36 (20%) patients and the median (IQR) length of hospitalisation was 20 (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) days. Oxygen support was administered low-flow in 40 (22%) patients, while 111 (61%) and 20 (11%) patients required CPAP/HFNC and invasive mechanical ventilation, respectively.…”
Section: Patient Characteristicsmentioning
confidence: 96%